The pandemic and wellbeing: Views from tourism employees - Christou, Prokopis A.; Rigou, Maria (My University, 2021)
This study sought to investigate wellbeing through the lens of people who have experienced the impacts of Covid-19 while working in an industry that was impacted severely by the effects of the pandemic. Study findings reveal the important and rather neglected role of the “sense of freedom” while examining, evaluating and fostering the wellbeing of individuals. This outcome has both societal, and tourism managerial implications.
Keywords: Tourism; Pandemic; Wellbeing